Political economy of the Vested Property Act in rural Bangladesh - Barkat, Abul.; Association for Land Reform and Development (Dhaka : Association for Land Reform and Development, 1997)
Study to assess the impact of the Vested Propert Act on land ownership, land transfer, and its social and economic consequences on the rural population in Bangladesh; includes related laws, acts, ordinances, orders, rules, and enactments
Includes bibliographical references (p. [187]-189).
Keywords: Enemy property; Alien property -- Bangladesh